Toxoplasma gondii C2 Domain Protein Deletion Mutant as a Promising Vaccine Against Toxoplasmosis in Mice - Yifan Luo; Mingfeng He; Shengqiang Yang; Jiahui Qian; Zhengming He; Jiayin Xu; Liyu Guo; Siyu Xiao; Rui Fang (Microbial Biotechnology)
ABSTRACT Toxoplasma gondii (T. gondii), a parasitic protozoan capable of infecting nearly all warm‐blooded animals, causes significant economic losses in livestock and poses a significant threat to both animal and public health. Despite its impact, no ideal vaccine is currently available to prevent toxoplasmosis. Vesicular transport plays a crucial role in the life cycle of T. gondii, and proteins involved in this process – such as those containing C2 domains – may serve as novel targets for the development of live attenuated vaccines. In this study, we evaluated the feasibility of a C2 domain‐containing protein (TGME49_203240) as a live attenuated vaccine candidate. Our findings suggest that TGME49_203240 may be involved in vesicular transport and that it is essential for T. gondii growth. Deletion of TGME49_203240 reduced parasite virulence and impaired tissue cyst formation in mice. Moreover, mice vaccinated with ME49Δ203240 were protected against the lethal challenge of the tachyzoites of T. gondii I, II, III strains and cysts of II strain. In addition, the ME49Δ203240 strain elicited robust immune responses, including the production of high levels of specific IgG antibodies and key cytokines (IFN‐γ, TNF‐α and IL‐12). These findings highlight TGME49_203240 as a promising target for the development of a live attenuated vaccine against T. gondii.